2020
DOI: 10.21037/tcr-20-2157
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of a combined fibrinogen and inflammation- based index in patients with metastatic breast cancer

Abstract: Background: The activation of inflammation and coagulation cascades plays an essential role in the development of various malignancies, including metastatic breast cancer (MBC). This retrospective study aimed to investigate the prognostic role of the combination of fibrinogen and the inflammation-based index in patients with MBC.Methods: A total of 176 patients with MBC were retrospectively reviewed. The clinical and pathological data of included patients were followed-up and analyzed. The plasma fibrinogen co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…After reviewing all the literature, 351 articles were included through screening of the title, abstract, and full text. Finally, 29 articles were included in this meta‐analysis after strict screening ( 18 20 , 24 49 ) ( Figure 1 ). The information of all the included literature was collected and pooled, and the basic characteristics are described in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing all the literature, 351 articles were included through screening of the title, abstract, and full text. Finally, 29 articles were included in this meta‐analysis after strict screening ( 18 20 , 24 49 ) ( Figure 1 ). The information of all the included literature was collected and pooled, and the basic characteristics are described in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…However, several previous meta-analyses only focus on breast cancer, and thus, there is still great uncertainty for the values of these potential prognostic biomarkers in MBC (2). Furthermore, although the ALC and NLR have been studied as prognostic markers of MBC in recent years, their prognostic values have not been determined uniformly, and different viewpoints still exist (18)(19)(20). Nevertheless, to the best of our knowledge, there is still a lack of relevant meta-analysis to provide relatively systematic and solid evidence regarding the prognostic value of ALC and NLR in MBC.…”
Section: Introductionmentioning
confidence: 99%
“…Its primary functions include hemostasis and wound healing by stabilizing blood clots. Other functions result from fibrinogen response to the microenvironment through many binding partners, particularly with integrins and receptors on cells associated with inflammation. , In addition to its involvement in inflammatory response, elevated serum fibrinogen levels have been linked to worse prognosis in cancers, such as such as metastatic breast cancer, lung cancer, and hepatocellular carcinoma (HCC). ,, Meta-analyses linking elevated serum fibrinogen in HCC patients to worse prognosis and in vitro studies showing elevated fibrinogen expression in HCC cells and HCC cell adherence to fibrinogen, have led to speculation of increased fibrinogen deposition by tumors. In the current study, imaging data demonstrated that fibrinogen peptides were detected in the HCC tumors, with minimal detection in the bridging fibrosis of S3 subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Kołodziejczyk et al ( 45 ) reported that the products of FIB degradation were associated with disease progression and metastasis. Liu et al ( 46 ) conducted a study that included 176 patients with metastatic breast cancer and showed that the FIB levels significantly increased after first-line therapy in patients with disease progression. Therefore, we hypothesize that FIB has a higher predictive value for the efficacy of second- or third-line therapy.…”
Section: Discussionmentioning
confidence: 99%